The Level of Politeness by Using Personal Pronouns on Campus - Harisal - Harisal; Wahyuning Dyah; Lien Darlina; Kanah Kanah (IZUMI, 2025)
Personal pronouns are a part of language. The use of the speaker’s pronouns to interlocutors is called first-person pronouns; The use of interlocutor’s pronouns to speakers is called second-person pronouns. Meanwhile, the use of personal pronouns to the object of conversation is called third-person pronouns. This research aimed to disclose the level of politeness by using personal pronouns on campus. It was located in the Tourism Department, State Polytechnic of Bali, and the object of the research is people with academic backgrounds who performed conversations by using personal pronouns. The research was descriptive-qualitative methodology and implemented the research techniques, including observation, documentation, literature, and triangulation. The research results reveal that several levels of politeness occur in the use of personal pronouns on campus. This is usually expressed when the speaker pays attention to the person he is talking to and the object of the conversation. Apart from that, the use of personal pronouns pays attention to several things so that there are no deviations in their use. The elements that must be considered include age, social status, and feelings. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor